Effect of Fibre Content on Mechanical Behavior of Slurry Infiltrated Fibrous Concrete - D, Elavarasi; Raja Mohan K, Saravana; A, Navatejareddy; R, Sushmitha (International Journal of Engineering and Technology, 2018)
Cement mortar or slurry is an essential material for production of Slurry Infiltrated Fibrous Concrete (SIFCON) structural components. However, there have been limited technical data available for deciding a suitable mix proportions and water cement ratio. For achieving a good quality of mortar mix or slurry with specific strength requirement and satisfactory level of workability for proper infiltration ability of cement slurry fibrebed. The preliminary study was carried out to select suitable mix and W/C from various mixes (1:1, 1:1.5 &1:2) and W/C (0.4, 0.45 & 0.5)on fresh and hardened properties of cement mortar. The optimum mix proportion and water cement ratio were obtained on workability (flow table test) and compressive strength of cement mortar are found to be as 1:1 and 0.40 respectively for fabrication of SIFCON. The main focus of this investigation on the behaviour of SIFCON contains various volume fraction of fibre content with an optimum mix(1:1) and W/C (0.4) under static loading. Hooked end steel fiber length of 30mm and tensile strength of 1050MPais used throughout the entire investigations. Cubes of 100 x 100 x 100mm for compressive strength and cylinders of 100mm diameter and 200mm height for split tensile strength were cast and tested at 3, 7 and 28 days. For flexural strength, three SIFCON beams of length 1200mm and cross section of 100mmx 200mm were cast and tested at 28 days under three point bending. The parameters like fracture energy, load deflection response, split tensile strength and compressive strength were found and compared the results with conventional mix. The test results observed that the strength performances were greatly improved due to addition of fibre by volume fraction in SIFCON matrix. Also developed the regression model from the experimental results to estimate the compressive and split tensile strength and compared the predicted values with the experimental values.Â Â